EFFECTS OF URBAN DEVELOPMENT AND SPATIAL CHARACTERISTICS ON URBAN THERMAL ENVIRONMENT IN CHIANG MAI METROPOLITAN, THAILAND - M. Srivanit; K. Hokao (Lowland Technology International, 2012)
Chiang Mai Metropolitan Area (CMMA) is the largest city in northern of Thailand, experiencing rapid urbanization that has resulted in remarkable the urban heat island (UHI) effect which will be sure to influence the regional climate, environment, and socio-economic development. In this study, we review the use of thermal remote sensing in the study of urban climates, focusing primarily on the UHI effect and an integrated remote sensing-based approach to investigate the effects of urban development and spatial characteristics on urban thermal environment. The LANDSAT ETM+ images from 2000 and 2006 were utilized to assess the surface urban heat island (SUHI) which will be further analyzed by investigating the relationships with several urban environment and development indices including; the Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), Density of Building (DenBldg), Floor Area Ratio (FAR) and Building Coverage Ratio (BCR) in the urban area of CMMA. Results show that the SUHI effect has become more prominent in areas with rapid urbanization in CMMA. It was found that the average of SUHI (Mean±S.D.) in the center of CMMA was about 20.52±1.05C in 2000, but this difference jumped to 28.08±1.50C in 2006. This could lead to an intensified the UHI effect in the urban areas. In order to analyze the relationship between surface temperatures with the spatial characteristic indices, the results of the correlation can understand impacts of the configuration and composition of spatial characteristics on local thermal environment which was the basic information for finding the reduction methods of urban temperature and the establishment of environmentally friendly urban planning in the future. Overall, remote sensing technology was an effective approach for monitoring and analyzing urban growth patterns and evaluating their impacts on urban climates.